COLD ROOM WAREHOUSE MANAGEMENT SYSTEM DEVELOPMENT: A CASE STUDY PBF BIO FARMA TBK - Alim, Nur
The government has planned a national vaccination program in line with the spread of the Covid-19 virus in Indonesia. Based on the data, the allocation of vaccine recipients in Indonesia is 181.5 million population, and the total need for vaccines reaches 426 million doses. PBF Bio Farma is responsible as a vaccine distributor from the Indonesian Ministry of Health and manages the storage of vaccines. The quantity of vaccine storage increases in line with the Covid-19 vaccination program and makes storage capacity overload. The average overload capacity is 25.26% of the ideal capacity. Overload capacity makes the cold room environment less conducive, and operator access is hampered due to the accumulation of goods in several areas. The design of this study is qualitative and quantitative research with the DMAIC framework scheme. Primary data were obtained from interviews and observations. Secondary data is obtained from the company's historical data and literature review. The current business analysis is explained based on the SCOR framework, RBV Analysis, PEST Analysis, and Root cause analysis. Based on the study, the overload causes are uncertainty of vaccine receipt and delivery schedule, manual checking in the receiving phase, improper layout, improper random storage policy, manual search, and no policy on order picking system. Based on the interview results, three leading solutions to overcome capacity overload are the new storage policy, relayout, and warehouse management system implementation (WMS). The new storage policy is a class-based storage method, making product search easier. After setting the storage policy, the following alternative solution is a re-layout. The layout design must support the class-based storage policy. A zoning system based on FSN Analysis must be implemented, and the FIFO principle as a Good Distribution Methode requirement becomes the basis for selecting flow racks. The next solution is related to the information system in the cold room, where WMS implementation can be a transition tool from manual systems to automation. WMS proposed in a cold room is a barcode system and application development. Implementing alternative solutions will be carried out according to the PDCA method. Based on calculations, there was an increase in cold room capacity from 4,824,000 vials to 5,844,823 vials, a rise of 21 percent from the current cold room capacity.